Exploiting Pincer Ligands to Perturb the Geometry at Boron. Issue 44 (20th July 2017) - Huang, Kexuan; Dutton, Jason L.; Martin, Caleb D.
Abstract: Boranes are ubiquitous in synthesis and materials but advancements in their development have been primarily restricted to the geometric energetic minima, trigonal planar complexes. This report discloses a class of boranes with expanded bond angles achieved by taking advantage of the structural rigidity of tridentate pincer ligands. The bonding of these novel boranes is investigated by X‐ray crystallography and computationally. Abstract : Boron Pinces One Out : Boranes are ubiquitous in synthesis and materials, but advancements in their development have been primarily restricted to the geometric energetic minima, trigonal planar complexes. This report discloses a new class of boranes with distorted geometries that are achieved by taking advantage of the structural rigidity of tridentate pincer ligands.